2009
DOI: 10.1038/onc.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

Expression, regulation and function of the ISGylation system in prostate cancer

Abstract: The androgen receptor (AR) plays a crucial role in the modulation of prostate cell proliferation and is involved in the development and progression of prostate cancer (PCa). An understanding of the complex regulation of AR provides novel treatment options for PCa. Here, we show (i) that the ubiquitin-like modifier, interferon-stimulated gene 15 (ISG15), and most enzymes involved in ISG15 conjugation were upregulated in tumor samples versus in non-malignant tissues of PCa patients and (ii) that the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 62 publications
(61 reference statements)
4
48
0
1
Order By: Relevance
“…Futhermore, increased expression of ISG15 and ISGylated protein have been shown in human cancer cell lines (19). In addition, in the current study, it was reported that the ISGylation system controled AR mRNA and protein expression and AR played a crucial role in the modulation of prostate cell proliferation and was involved in the development and progression of prostate cancer (20). In our study, we also showed a positive association between the expression of ISG15 and PC cell growth or survival.…”
Section: Discussionsupporting
confidence: 72%
“…Futhermore, increased expression of ISG15 and ISGylated protein have been shown in human cancer cell lines (19). In addition, in the current study, it was reported that the ISGylation system controled AR mRNA and protein expression and AR played a crucial role in the modulation of prostate cell proliferation and was involved in the development and progression of prostate cancer (20). In our study, we also showed a positive association between the expression of ISG15 and PC cell growth or survival.…”
Section: Discussionsupporting
confidence: 72%
“…In vitro cell line-based studies have revealed contrary roles for protein ISGylation in tumorigenesis (27)(28)(29). However, these conclusions depend largely on cell-autonomous events, such as cell proliferation, cell death, and cell evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ISGylation is strongly enhanced upon pathogen infection and cellular stress related o IFN induction (25). Several in vitro studies using cell lines and human cancer samples have begun to reveal anti-and protumorigenic roles of ISGylation (27)(28)(29). However, in vivo studies of protein ISGylation in tumorigenesis are relatively rare and have become a pressing need for understanding the role of ISG15 in malignant progression.…”
mentioning
confidence: 99%
“…For example, while some reports suggest that like ubiquitylation, ISGylation may function in protein turnover (18), it may also play a previously unrecognized role in protein stability (17). The latter has been explored in systems of bladder, oral, prostate, and breast cancers, where high levels of ISG15 and its conjugates have been detected, suggesting a link between ISG15 and tumorigenesis (19)(20)(21)(22)(23)(24). For example, Kiessling and colleagues have shown that in prostate cancer, overexpression of UbE1L increased androgen receptor levels in an ISG15-dependent manner, implying that ISGylation promotes androgen receptor overexpression in cancer cells.…”
Section: Introductionmentioning
confidence: 99%